CD44high/ALDH1high head and neck squamous cell carcinoma cells exhibit mesenchymal characteristics and GSK3β‐dependent cancer stem cell properties. (24th September 2015) - Seino, Sayaka; Shigeishi, Hideo; Hashikata, Miho; Higashikawa, Koichiro; Tobiume, Kei; Uetsuki, Ryo; Ishida, Yoko; Sasaki, Kazuki; Naruse, Takako; Rahman, Mohammad Zeshaan; Ono, Shigehiro; Simasue, Hiroshi; et al.
Abstract : Background: CD44 and aldehyde dehydrogenase 1 (ALDH1) have been shown to be useful markers for identification of cancer stem cells (CSCs). We previously reported that glycogen synthase kinase 3β (GSK3β) is involved in regulation of the self‐renewal ability of head and neck squamous cell carcinoma (HNSCC) CSCs. The purpose of the present study was to clarify the role of GSK3β in CD44 high /ALDH1 high HNSCC cells. Methods: Cells with greater expression of CD44 and higher ALDH1 enzymatic activity were FACS sorted from the OM‐1 HNSCC cell line. The self‐renewal ability of CD44 high /ALDH1 high cells was then examined using a tumor sphere formation assay. mRNA expressions of the stem cell markers Sox2, Oct4, and Nanog, as well as GSK3β were evaluated by real‐time RT‐PCR. Results: CD44 high /ALDH1 high cells exhibited higher tumor sphere forming ability and increased expression of stem cell markers as compared with CD44 high /ALDH1 low cells. Interestingly, spindle‐shaped cells positive for vimentin were found in the CD44 high /ALDH1 high but not the CD44 high /ALDH1 low cell population. In addition, the ALDH1 activity and sphere forming ability of CD44 high /ALDH1 high cells was significantly inhibited by GSK3β knockdown. On the other hand, CD44 high /ALDH1 low cells exhibited high epidermal growth factor receptor (EGFR) expression and increased cell growth. Conclusions: Our results show that GSK3β plays a major role in maintenance of stemness of CD44 high /ALDH1 high HNSCC cells. Additionally, they indicate a close relationship between CSC and mesenchymal characteristics in HNSCC.